Advancing joint disease diagnosis: Molecular profiling and biomarker identification in synovial fluid using Raman spectroscopy - Al Ghaithi, Ahmed K.; Almaskari, Sultan M.; Almutani, Mohammad M.; Al Bimani, Atika M.; AL-Jabri, Zaaima; Al Badi, Khoula S.; Husband, John (Journal of Musculoskeletal Surgery and Research)
Objectives: Synovial fluid (SF) analysis is crucial for diagnosing various joint diseases. This research delved into using Raman spectroscopy (RS) as a primary method for molecular profiling of SF and identifying significant biomarkers. The findings from this research have the potential to expand the utility of RS in diagnosing a diverse range of joint conditions. Methods: The SF samples were collected from patients undergoing knee joint surgeries and analyzed using RS coupled with a video microsampling system. Various strategies were implemented to minimize background fluorescence interference, a common challenge in biofluid RS analysis. Results: The spectral characteristics of fresh and overnight dry SF samples were compared revealing a reduction in background fluorescence in the dried samples. However, certain important signals were found to be absent due to overlap between Raman bands. The analysis showed distinct spectral features associated with hyaluronic acid, glycosaminoglycans, collagen, and proteins, highlighting their potential as biomarkers for joint diseases. Conclusion: Our study highlights the effectiveness of RS as a promising non-invasive method for analyzing SF. We have pinpointed specific biomarkers critical for joint health and disease paving the way for RS to potentially revolutionize the diagnosis and monitoring of joint pathologies. Despite the focus on osteoarthritis, the implications of this research extend to other complex joint diseases necessitating further investigation to enhance diagnostic precision and patient care.